Free To Be… You and Me: the Best-Selling Record and Popular Show Which Made America Rethink Gender Stereotypes (American & British Studies Annual, 2021)
Long before wide-spread discussion of “toxic masculinity,” “mansplaining” and “gender identity,” we had Free To Be... You and Me by Marlo Thomas and friends. This paper will examine the cultural and historical impact of this ground-breaking record album, illustrated booklet and television special from 1972 and 1974 respectively. This project was the brainchild of the popular actress and social activist Marlo Thomas, with the proceeds from the project going to support the Ms. Foundation For Women, an extremely influential feminist organization. A number of leading entertainers participated in the project: Michael Jackson, Diana Ross, Alan Alda, to name but a few. Although initially met with great skepticism, the record and consequent television show became huge hits, becoming the sound-track for a generation of children growing up in the 1970s. I would argue that this project, more than anything else up until that time contributed to feminist consciousness raising and awareness of gender stereotyping and still has much to teach us today.
Keywords: feminism; gender identity; television; children’s entertainment